The behavior of polyurethane foam-filled glass-fiber-reinforced polymer crossarm subjected to lightning transient voltage - Abd Rahman, Muhammad Syahmi; Ab Kadir, Mohd Zainal Abidin; Abd Rahman, Muhamad Safwan; Osman, Miszaina; Ungku Amirulddin, Ungku Anisa; Mohd Nor, Shamsul Fahmi; Mohd Zainuddin, Noorlina (MDPI AG, 2021)
The demand for composite materials in high-voltage electrical insulation is escalating over the last decades. In the power system, the composite glass-fiber-reinforced polymer has been used as an alternative to wood and steel crossarm structures due to its superior properties. As a composite, the material is susceptible to multi-aging factors, one of which is the electrical stress caused by continuous and temporary overvoltage. In order to achieve a better insulation performance and higher life expectancy, the distribution of the stresses should firstly be studied and understood. This paper focuses on the simulation work to better understand the stress distribution of the polyurethane foam-filled glass-fiber-reinforced polymer crossarm due to the lightning transient injection. A finite-element-based simulation was carried out to investigate the behavior of the electric field and voltage distribution across the sample using an Ansys Maxwell 3D. Electrical stresses at both outer and inner surfaces of the crossarm during the peak of lightning were analyzed. Analyses on the electric field and potential distribution were performed at different parts of the crossarm and correlated to the physical characteristics and common discharge location observed during the experiment. The results of the electric field on the crossarm indicate that both the outer and internal parts of the crossarm were prone to high field stress.